MENDUGA KUALITAS LAYANAN MASKAPAI DOMESTIK MENGGUNAKAN JARINGAN SYARAF TIRUAN - YASMAN, MULIA; KENCANA, I PUTU EKA NILA; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika, 2023)
Measurement of service quality is very important because it can determine the accuracy between consumer perceptions and expectations when receiving information before using the items or services. Measurement of service quality can be done using the service quality method developed by Parasuraman et al. (1990). The independent variables used refer to the dimensions of service quality, namely reliability, assurance, tangiable, empathy, and responsiveness. While the dependent variable is satisfaction. The measurement of service quality using an artificial neural network with a backpropagation algorithm is carried out by obtaining input data and target data from calculations using service quality. Testing on the artificial neural network is carried out in two stages, namely training data and testing data. The results are then compared with the target data on the service quality method to determine accuracy.